2018
DOI: 10.1021/acs.orglett.8b00982
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Tandem Reaction of Three Aryl Iodides Involving Triple C–H Activation

Abstract: A novel palladium-catalyzed tandem reaction of N-(2-iodoaryl)acrylamides with two aryl iodides for the synthesis of spirooxindole has been achieved. The reaction underwent the process of triple C-H activation and four C-C bond formations based on the double trapping of transient spirocyclic palladacycles which are obtained through remote C-H activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 78 publications
0
19
0
Order By: Relevance
“…14 Yang and Liang have applied this strategy for oxindole synthesis, and two aryl groups derived from 28 were incorporated in the final products. 15 In their subsequent study, Lautens and co-workers found that intermediate 26 could be trapped by Me 6 Si 2 or Me 6 Ge 2 , thus disilylation or digermanylation of 23 could be easily realized. 16a Shortly after this study, Liang and Yang reported a palladium-catalyzed domino Heck-disilylation and borylation of alkenetethered 2-(2-halophenyl)-1H-indoles.…”
Section: Short Review Synthesismentioning
confidence: 99%
“…14 Yang and Liang have applied this strategy for oxindole synthesis, and two aryl groups derived from 28 were incorporated in the final products. 15 In their subsequent study, Lautens and co-workers found that intermediate 26 could be trapped by Me 6 Si 2 or Me 6 Ge 2 , thus disilylation or digermanylation of 23 could be easily realized. 16a Shortly after this study, Liang and Yang reported a palladium-catalyzed domino Heck-disilylation and borylation of alkenetethered 2-(2-halophenyl)-1H-indoles.…”
Section: Short Review Synthesismentioning
confidence: 99%
“…343 These works were followed by Liang and Yang's report on the synthesis of 109 in a triple C-H activation approach where the alkylPd II intermediate is intercepted by 2 further equivalents of aryl iodide (Scheme 69). 344 Another approach is Pd-catalysed migratory insertion of diazo compounds and Michael addition. 345 Chiral hypervalent iodine mediated.…”
Section: Spirocylohexanyl Oxindolesmentioning
confidence: 99%
“…In the first case, the migratory insertion of unsaturated coupling partners, such as alkynes, arynes, diazocompounds or even fullerenes, into the Pd-C bond of intermediates 122 lead to spirocyclic scaffolds I (Scheme 96). [107a,125] In those cascade reactions where the coupling partner (such as TMS-TMS, [120d] CH 2 Br 2 [126] or haloarenes, [127] among others [128] ) can add oxidatively to the Pd(II) center in 122 to give the Pd(IV) species 123, a variety of functionalized organic products II can be obtained.…”
Section: Selected Examples Of Catalytic Reactions Involving Cc-palladacyclic Intermediatesmentioning
confidence: 99%